ABDÜLHAK HÂMİD TARHANIN ŞİİRLERİNİN İNANÇ ÖLÜM, TABİAT VE KADIN TEMALARI BAKIMINDAN İNCELENMESİ - GÜL, MEHMET (Fırat Üniveristesi, 2013)
Tanzimat Edebiyatının en aykırı şairi olan Hâmid, şiirlerinde bireysel konuları ele almış ve sosyal ve siyasi konulardan uzak kalmıştır. Şiirlerinde daha çok her insanın ayrılmaz parçaları olan inanç, ölüm, tabiat ve kadın temalarını işlemiştir. Hâmid bu temaları daha çok felsefi bir nazarla ele almıştır. Onun şiirlerinde İnanç konusunda isyan ve teslimiyet, ölüm konusunda tahammülsüzlük, tabiat konusunda sonsuzluk ve kadın konusunda doyumsuzluk göze çarpar. Anahtar Kelimeler: Hâmid, ?nanç, Ölüm, Tabiat, Kadın.

Hâmid, the most contradictious poet of Tanzimat Edebiyatı had poems clealt with individual issues. He was also far away from the social and political issues. In his poem, he mentioned about the inseparable parts of any human being such as faith, death, nature and woman themes. Hâmid adressed these themes in a more philosophicial perspective. Rebellion and resignation in the subject faith; intolarance death; eternity fort he nature and dissatisfaction fort he subject woman are the naticable points in his poems. Key Words: Hâmid, Faith, Death, Nature, Woman.
Themes analysis in nature women, faith and the death Abdülhak Hâmid Tarhan's poems
Keywords: Türk Dili ve Edebiyatı